2018
DOI: 10.1214/18-ejp147
|View full text |Cite
|
Sign up to set email alerts
|

Evolution systems of measures and semigroup properties on evolving manifolds

Abstract: An evolving Riemannian manifold (M, g t ) t∈I consists of a smooth d-dimensional manifold M, equipped with a geometric flow g t of complete Riemannian metrics, parametrized by I = (−∞, T ). Given an additional C 1,1 family of vector fields (Z t ) t∈I on M. We study the family of operators L t = ∆ t + Z t where ∆ t denotes the Laplacian with respect to the metric g t . We first give sufficient conditions, in terms of space-time Lyapunov functions, for non-explosion of the diffusion generated by L t , and for ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Only recently, some of these properties and equivalences have been extended to the heat flow on time-dependent Riemannian manifolds, for example, by Cheng and Thalmaier [9], Haslhofer and Naber [12], McCann and Topping [17], and Cheng [8]. The authors of the current paper had been the first to study the heat flow on time-dependent metric measure spaces [14], to introduce the time-dependent counterpart of synthetic lower Ricci bounds, and to derive various functional inequalities equivalent to it.…”
Section: Settingmentioning
confidence: 99%
“…Only recently, some of these properties and equivalences have been extended to the heat flow on time-dependent Riemannian manifolds, for example, by Cheng and Thalmaier [9], Haslhofer and Naber [12], McCann and Topping [17], and Cheng [8]. The authors of the current paper had been the first to study the heat flow on time-dependent metric measure spaces [14], to introduce the time-dependent counterpart of synthetic lower Ricci bounds, and to derive various functional inequalities equivalent to it.…”
Section: Settingmentioning
confidence: 99%
“…Since g is arbitrary, this proves the first two claims of the theorem in the case of bounded u ∈ D(E). The claim (9) for bounded u ∈ L 2 (X) follows by applying the latter estimate with s + δ in the place of s to the function P s+δ,s u as δ → 0, which lies in D(E) and from gP t,s+δ ((P s+δ,s u) 2 )dm t → gP t,s (u 2 )dm t which in turn is a consequence of the continuity of δ → P * t,s+δ g and of δ → P s+δ,s u in L 2 and the uniform boundedness of the latter in L ∞ .…”
Section: Preliminariesmentioning
confidence: 99%
“…Only recently, some of these properties and equivalences have been extended to the heat flow on time-dependent Riemannian manifolds, e.g. by Cheng & Thalmaier [9], Haslhofer & Naber [12],…”
Section: Introduction 1settingmentioning
confidence: 99%
“…In [5], the first two authors investigated existence and uniqueness of evolution systems of measures. In particular, they found that W 1 -contraction of the distance helps to prove uniqueness properties (see [5] for details).…”
Section: Introductionmentioning
confidence: 99%
“…In [5], the first two authors investigated existence and uniqueness of evolution systems of measures. In particular, they found that W 1 -contraction of the distance helps to prove uniqueness properties (see [5] for details). Since now the W 1 -contraction is established even in cases when the lower bound of the curvature may be negative, this allows to improve the result in [5] where a uniform lower curvature bound had been imposed for each time.…”
Section: Introductionmentioning
confidence: 99%